A sentimental affair: Vérité - Counter, A (Columbia University, 2011)
The despicable crime that represents Dreyfus's alleged treason is a sex crime, while the novel's Utopian future is constructed around what Zola takes to be a frank, humanistic model of sexuality, supposedly one specially conducive to (if not synonymous with) human happiness. Yet as we shall see, in articulating more explicitly the erotic content that we may well consider to have silently inhered in sentimental writing since its origins in the late eighteenth century (and especially with Rousseau, whose philosophical and stylistic influence is to be felt everywhere in Vérité), Zola chooses to eliminate many of the possibilities of that eroticism in favor of a relentlessly normative, procreative heterosexuality.\n Now, such a rediscovery is of undeniably paramount importance if the gradual liberation of Zola's canonical fiction from reductive critical frameworks is to continue.